Transgenic mice as an alternative to monkeys for neurovirulence testing of live oral poliovirus vaccine: validation by a WHO collaborative study - Dragunsky Eugenia; Nomura Tatsuji; Karpinski Kazimir; Furesz John; Wood David J.; Pervikov Yuri; Abe Shinobu; Kurata Takeshi; Vanloocke Olivier; Karganova Galina; Taffs Rolf; Heath Alan; et al. (The World Health Organization, 2003)
OBJECTIVE: Extensive WHO collaborative studies were performed to evaluate the suitability of transgenic mice susceptible to poliovirus (TgPVR mice, strain 21, bred and provided by the Central Institute for Experimental Animals, Japan) as an alternative to monkeys in the neurovirulence test (NVT) of oral poliovirus vaccine (OPV). METHODS: Nine laboratories participated in the collaborative study on testing neurovirulence of 94 preparations of OPV and vaccine derivatives of all three serotypes in TgPVR21 mice. FINDINGS: Statistical analysis of the data demonstrated that the TgPVR21 mouse NVT was of comparable sensitivity and reproducibility to the conventional WHO NVT in simians. A statistical model for acceptance/rejection of OPV lots in the mouse test was developed, validated, and shown to be suitable for all three vaccine types. The assessment of the transgenic mouse NVT is based on clinical evaluation of paralysed mice. Unlike the monkey NVT, histological examination of central nervous system tissue of each mouse offered no advantage over careful and detailed clinical observation. CONCLUSIONS: Based on data from the collaborative studies the WHO Expert Committee for Biological Standardization approved the mouse NVT as an alternative to the monkey test for all three OPV types and defined a standard implementation process for laboratories that wish to use the test. This represents the first successful introduction of transgenic animals into control of biologicals.